Antimicrobial activity of kaempferol and resveratrol in binary combinations with parabens or propyl gallate against Enterococcus faecalis. (March 2016) - del Valle, Pilar; García-Armesto, María Rosario; de Arriaga, Dolores; González-Donquiles, Cármen; Rodríguez-Fernández, Pablo; Rúa, Javier
Abstract: Antimicrobial activity of two natural phenolic compounds (resveratrol and kaempferol) and three synthetic (propyl gallate, propyl- and heptyl paraben) against two strains of Enterococcus faecalis were analyzed by checkerboard and time-kill methods. Heptyl paraben was the most effective followed by resveratrol, kaempferol, propyl gallate and propyl paraben, according to their minimal inhibitory concentrations (MICs) ranging from 13.4 μg mL −1 (heptyl paraben) to 881.82 μg mL −1 (propyl paraben). Kaempferol plus resveratrol and binary combinations of each one with propyl gallate or parabens showed no interaction effects by the checkerboard method. Kaempferol and resveratrol in combination produce a growth inhibition in cation adjusted Mueller-Hinton broth and in skimmed milk, characterized by an increase in the lag phase and a decrease in the maximum specific growth rate. Heptyl paraben alone or in combination with kaempferol showed bacteriostatic effects. Kaempferol combined with resveratrol, propyl gallate, propyl- or heptyl paraben produces antagonistic effect in antioxidant activity, obtaining the highest effect with the two parabens (approximately a 25% reduction). The antagonistic effects analyzed by regeneration mechanisms are discussed in relation to the increase of the antimicrobial activity shown by the binary combinations tested against the two strains of E. faecalis. Highlights: Binary mixtures of phenolic antioxidants against two Enterococcus faecalis strains were analyzed. Binary combinations of phenolics show no interaction by checkerboard method. Kaempferol + resveratrol produce a growth inhibition in MHB and milk by time-kill method. Heptyl paraben alone or in combination with kaempferol show bacteriostatic effect. Binary combinations with kaempferol show antagonistic effects on antioxidant activity.